KARAWITAN KARATON KASUNANAN DAN PURA MANGKUNEGARAN PASCA PERJANJIAN GIYANTI - Bambang Sosodoro (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2013)
This paper is an examination of the results found in the study entitled: â€œKarawitan Karaton dan Pura Mangkunegaran Studi Garap Karawitan Tari Srimpiâ€ (The Gamelan Music of the Karaton and Mangkunegaran Palaces: A Study In Accompaniment for the Srimpi Dance). This research is a field study examining the gamelan music of the Surakartan palaces (the Karaton and the Mangkunegaran). This topic was chosen based on historical and musical importance, in that the repertory and performance practice at these two institutions reveal interesting and highly current points of discussion. The Karaton Surakarta and the Mangkunegaran Palace are two important pillars of the Surakarta identity in gamelan music practice. Performance practice existing at the Karaton and Mangkunegaran is a fascinating topic of research from many different angles. This is due to the fact that these two palaces both represent Surkarta-style gamelan practice and yet produce very different results. The musical idioms and vocabulary involved in playing the different parts, the repertory, and the interpretation of pieces is much the same, but the resulting resulting musical aesthetic and feeling is quite different. Performance practice issues became ever more involved and interesting once there was a bonding between the Yogyakarta Principality and the Mangkunegaran, through marriage, as at this time both physical and aesthetic commonalities emerged between these two institutions. Because of the family connection in marriage, a more Yogyanese style emerged at the Mangkunegaran Palace. Although some may say identical to Yogya, in fact many elements of Surakarta style remained. This work attempts to offer the background to the emergence of performance practice at the Karaton and Mangkunegaran post Giyanti agreement. In order to present this background, a contextual approach is used, outlining the various factors that led to the development of differences between the two centers.Key words: historis perspective, style of karawitan